Finite element and boundary element methods for elasto-plastic stress analysis of two-dimensional and axisymmetric problems - Husain, Imad Ahmed (Cranfield University, 1989)
This work dealt with elasto-plastic analysis of 2-dimensional and axisymmetric problems using the finite-element and boundary-element techniques. The analysis is based upon a vide range of yield criteria and hardening rules so as to be suitable for most engineering materials. Many accuracy measures have been employed with the boundary-integral equation derivations, such as isoparametric boundary elements, singular quadrature, corner models, finite-difference schemes for internal stress evaluation, high-order integration cells, and the use of boundary-integral expressions for domain loading terms. A programming package has been developed vith its own mesh generator and results plotter. The package has been validated using several case studies including a benchmark test case recommended by NAFEMS. The finite-element analysis of elasto-plastic problems proved to be more stable and reliable than the corresponding boundary-element analysis.